IMPROVEMENT OF MEDICAL WASTE STORAGE PROCEDURES - Sančanin, Branislav; Sancanin, Aleksandra (Sanamed, 2023)
Medical waste is all waste generated by healthcare institutions related to the performance of medical-technical actions in the field of diagnostics, therapy, or research activities. The adequate disposal of medical waste is an issue for virtually all Southeastern European countries primarily because these countries lack the necessary capacities for removing medical waste. The paper aims to review the results and experiences of treating medical waste, as well as the potential risks to patients and medical and non-medical personnel. Implementing a safe medical waste management system could significantly improve the quality of healthcare services and the health of patients, and preserve the environment. The use of steam sterilization has been suggested to reduce the content of biological agents in the waste to an acceptable level by thermal treatment, that is, to achieve biological inactivation.